« fake news », lies and propaganda : Health Related Information Verification Behaviours (HRIVB) models among youth on social networking sites - Wan Mokhtar, Wan Ikhlas; Arshad, Mohd Mursyid; Mohd Zawawi, Julia Wirza; Ismail, Ismi Arif; Ahmad Ghazali, Akmar Hayati (Human Resource Management Academic Research Society, 2024)
Covid19 pandemic has caused more than 2 million death across the globe and its information dissemination needs to be accelerated as it might reduce the infection risks and social media can play a significant role. Youth are closely attached to social media and are expected to be the main receiver of health-related information. Understandably, it is important for them to verify first the information they received before using or sharing it or otherwise there is a possibility of fake news/information being spread and create chaos to the community. Moreover, the existing models on health related information verification behaviour (HRIVB) have several deficiencies and improvements are needed to suit the current setting. Hence, this review focuses on what are the complexity of the existing models and the background of youths using these models, why there are exclusions of some importants factors and what are the current concerns on social media